A Frailty Index Identifies Patients at High Risk of Mortality after Tracheostomy. (16th January 2014) - Johnson, Matthew S.; Bailey, Travis L.; Schmid, Kendra K.; Lydiatt, William M.; Johanning, Jason M.
Abstract : Objective: To evaluate the utility of a modified frailty index as an indicator of postoperative mortality in patients undergoing tracheostomy. Study Design: Case series with chart review. Setting: Tertiary care veterans hospital. Subjects and Methods: A chart review was conducted of consecutive tracheostomies performed between April 2007 and September 2012. A modified frailty index consisting of 11 items based on the Revised Minimum Data Set Mortality Rating Index (MMRI‐R) was retrospectively applied using the patient's status immediately prior to tracheostomy. The resultant 6‐month calculated mortality risk was compared with both the Veterans Health Administration Surgical Quality Improvement Program's (VASQIP) 30‐day calculated mortality and actual mortality. Results: One hundred consecutive tracheostomies were analyzed. No patients were excluded. Sixty‐nine patients died within the study period, with 1‐, 6‐, and 12‐month mortality rates of 25%, 43%, and 59%, respectively. The average calculated 6‐month mortality risk using the modified frailty index was 40.5% for nonsurvivors compared with 25.4% for survivors ( P =. 001). Both the VASQIP calculator and modified frailty index differentiated mortality risks between patients without head and neck cancer who survived less than 6 months versus those who survived longer than 6 months ( P =. 006 and. 01). However, neither the VASQIP nor the modified frailty index differentiated mortality risks for head and neck cancer patients who survived less than 6 months versus greater than 6 months ( P =. 94 and. 26). Conclusion: A modified frailty index identifies patients without head and neck cancer at high risk of postoperative mortality after tracheostomy.